Valuing Employees with Disabilities: A Chain Effect of Pro-Disability Climate on Organizational Commitment - Wittmer, Jenell Lynn-Senter; Lin, Canchu (Disability Studies Quarterly, 2017)
Previous organizational research has focused heavily on organizational commitment, for employees in general, as well as for specific minority groups. However, there is a large gap in the research literature concerning the organizational commitment of people with disabilities. The current study contributes to the literature both by investigating the predictors of reported organizational commitment of people with disabilities, as well by examining organizational-level predictors, rather than individual-level phenomena. Additionally, rather than examining legal or compliance issues related to people with disabilities, as is found in most previous research, the current study examines contextual predictors of organizational commitment, pro-disability climate, pro-disability technology, and availability of flexible work arrangements. Structural equation modeling results suggest that there is a chain effect of pro-disability climate, which impacts the organizational commitment of people with disabilities through pro-disability technology and flexible work arrangements. Implications for both research and human resource practitioners are discussed.